Types Of Accents In Japanese Learners’ Speech On Target Words In Medan City - Siti Muharami Malayu , Yuddi Adrian Muliadi (Migration Letters, 2024)
This research aims to examine variations in speech accents in the context of Japanese language learning in Medan City. The main focus includes characteristics of Japanese accents, factors influencing the formation of speech accents, and implications of the findings for teaching methods. Through this approach, this research seeks to understand how Japanese language learners in Medan City face and overcome the challenges of speech accents. The research methodology uses a qualitative approach by interviewing students and analyzing recorded speech data. It is hoped that the results will contribute to a deeper understanding of the dynamics of Japanese language learning outside of its native environment.